Impact of Health Education on Insurance on the Geriatric; A Content Analysis of Radio Health Programs ‘Mpon Te Sen’ (How is Your Health) - Afful, Gyimah William; Lulin, Zhou; Abakah, Stephen; Amoah, Erica Panin (Advances in Social Sciences Research Journal, 2022)
Health education has been a critical topic of discussion nowadays in Ghana and the global community as well. Educating individuals, especially the aged, is significant and helps reduce the country’s death rate. Many aged individuals have no idea about how to handle their health system and also if they do, cannot go by it themselves. This research explores the impact of health education on insurance for the aged, using a program aired on Peace FM (a radio station in Ghana) ‘Mpon te sen’ (HOW IS YOUR HEALTH) to educate both young and old. The study highlights the grievances most elderly ones share on the program. The study used qualitative content analysis to evaluate the radio program and analyzed callers’ responses to questions asked about characteristics using SPSS (version 25.0). The study, also, explored challenges and impacts on health education. Lastly, the study recommended offering proper care to older Ghanaians, and health personnel should be taught geriatric care through seminars. In aged care, bottom-up techniques should be used, with the old and their family’s concerns and opinions taken into account.